MODERN GREEK HISTORIOGRAPHY ON OTTOMAN MACEDONIA Some considerations after 1995 (Annual of the Faculty of Philosophy in Skopje, 2015)
The knowledge of historiography, anthropology, and cartography that deal with the Macedonian past is very important not only for historians, but also for the public. For example, very often through historiography, one can feel the pulse of one state or society towards another, in this case Macedonia. The neighboring scientific views are not exceptions to this fact. Unfortunately, with the exception of the more liberal thinkers, historiography, anthropology, and cartography very often are under the influence, purposely or not, of the political situation in the state, even in those that consider themselves as the most liberal ones. That is the case with the contemporary Greek science that deals with the Macedonian past, which in general is treated, as a part of the Greek past.
Keywords: GREECE; MACEDONIA; HISTORIOGRAPHY